Pengaruh Model Project Based Learning Berbantuan Media Video Animasi terhadap Keterampilan Menulis Teks Puisi Siswa Kelas X SMA Negeri Pariaman - Rahman, Annisa Ainur; Afnita, Afnita (Journal of Education Language and Innovation, 2024)
This research is motivated by the low poetry writing skills of tenth-grade students at SMA Negeri 5 Pariaman, which are attributed to inappropriate teaching models, students’ fear of learning activities, lack of enthusiasm, and low creativity in writing poetry. These factors indicate the need for more effective teaching approaches to improve students’ learning outcomes in poetry writing. This study aims to describe the poetry text writing skills of class X students of SMA Negeri 5 Pariaman using the Project Based Learning model assisted animated video media, to describe the poetry text writing skills of class X students of SMA Negeri 5 Pariaman using conventional learning models, and to explain the effect of the Project Based Learning model assisted by animated media on the poetry text writing skills of class X students of SMA Negeri 5 Pariaman. This type of research is quantitative research with an experimental method.